Bacterial Inhibitors in Lake Water - Klein, Theodore M. (1986)
The populations of six bacterial genera fell rapidly after their addition to sterile lake water but not after their addition to buffer. The decline in numbers of two species that were studied further, Klebsiella pneumoniae and Micrococcus flavus, occurred even when the buffer was added to sterile lake water. The inhibition of K. pneumoniae by substances in lake water varied with the season of the year, and the rate and extent of decline of both species were different in sterile samples of different lakes. The extent of reduction in the density of K. pneumoniae was independent of initial population size and was diminished by the addition of 10 μg of glucose per ml of lake water. The toxin was removed from lake water by dialysis and by a cation-exchange resin but not by an anion-exchange resin, and it was destroyed by heating. The inhibition of K. pneumoniae was not evident in lake water buffered at a pH value above 8.0. We suggest that toxins may be important in determining the composition of the bacterial community of lakes.